Role strain in talent development : a psycho-social perspective on the dual careers of junior elite athletes - Van Rens, F. E. C. A. (2015)
This thesis developed and validated the Role Strain Questionnaire for Junior Athletes (RSQ-JA), an instrument designed to measure the role strain junior elite athletes experience in their multiple life domains (e.g., school, sport, family and friendships). Results supported a 22-item five factor structure for the RSQ-JA. These factors reflected five components of role strain, namely; (i) overload in school, (ii) overload in sport and between roles, (iii) conflict, (iv) underload, and (v) ambiguity. The RSQ-JA therefore provides the first valid measure to assess the role strain associated with the dual careers of junior elite athletes.